2015
DOI: 10.1111/jog.12834
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian diet and reduced uterine fibroids risk: A case–control study in Nanjing, China

Abstract: The original evidence from this epidemiological investigation shows that a high consumption of broccoli, cabbage, Chinese cabbage, tomato and apple seems to be a protective factor for uterine fibroids. We suggest that greater intake of fresh fruits and cruciferous vegetables may be able to reduce the incidence of uterine fibroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Several studies support an inverse association between leiomyoma and a great intake of fruits and vegetables, particularly for citrus fruit [46], cruciferous vegetables (broccoli, cabbage, and Chinese cabbage), tomatoes, and apples [46]. Fruit and vegetables contain various nutrients that may decrease fibroid risk through inhibition of proliferation, apoptosis, or hormone-dependent pathways [47].…”
Section: Lifestyle and Dietmentioning
confidence: 99%
“…Several studies support an inverse association between leiomyoma and a great intake of fruits and vegetables, particularly for citrus fruit [46], cruciferous vegetables (broccoli, cabbage, and Chinese cabbage), tomatoes, and apples [46]. Fruit and vegetables contain various nutrients that may decrease fibroid risk through inhibition of proliferation, apoptosis, or hormone-dependent pathways [47].…”
Section: Lifestyle and Dietmentioning
confidence: 99%
“…The positive impact of an active health-promoting lifestyle on the development of UFs is a trendy subject to explore. Exposure to different environmental and nutritional factors, such as plastic products, cosmetics, and other chemicals, as well as the intake of soybean milk, food additives, sweeteners, and preserved foods can increase the risk of UFs [4,30]. Furthermore, the incidence of UFs has been shown to be greater in populations consuming more red meat, for example, beef [31].…”
Section: Diet Healthy Lifestyle and Uterine Fibroids: An Overviewmentioning
confidence: 99%
“…Several studies have shown a protective effect of vegetable and fruit intake against uterine leiomyomas, most notably with citrus fruit, apples, cabbage, broccoli, and tomatoes [ 30 , 31 , 32 ]. In the US Black Women’s Health Cohort Study, the frequency of food items has been determined on the premise of how many servings are consumed per day or month among women before menopause [ 30 ].…”
Section: Diet and Nutrition In Uterine Leiomyomamentioning
confidence: 99%